Expression and Function of Neuron-Glia-Related Cell Adhesion Molecule (NrCAM) in the Amygdalar Pathway - Mohan, Vishwa; Gomez, Julia R.; Maness, Patricia F. (Frontiers in Cell and Developmental Biology, 2019)
Neuron-glial related cell adhesion molecule (NrCAM) is a candidate autism risk factor that promotes axon guidance through cytoskeletal linkages in developing brain but its role in limbic circuitry has not been investigated. In situ hybridization and immunofluorescence staining showed that NrCAM is expressed in the developing amygdalar pathway of mouse embryos during outgrowth of projections in the ST, a major limbic tract that interconnects the central amygdala with key targets in the bed nucleus of the stria terminalis (BNST). Analysis of fiber tracts in NrCAM mutant mice by Neurofilament protein immunohistochemistry showed pronounced defasciculation and misprojection of fibers in the ST. The defasciculation phenotype may result from impairment in NrCAM homophilic inter-axonal adhesion or axon repulsion from the secreted ligand Semaphorin3F, which is expressed in limbic areas in proximity to the ST. Behavioral testing indicated that NrCAM null mice were impaired in context-dependent fear conditioning, in accord with altered amygdala-BNST connectivity, but displayed normal cued (tone-shock) conditioning. Results are consistent with the novel finding that NrCAM mediates fasciculation of axon fibers in the ST important for proper amygdalar-BNST circuitry and response to contextual fear conditioning.